2016
DOI: 10.1002/adom.201500726
|View full text |Cite
|
Sign up to set email alerts
|

Neodymium‐Based Stoichiometric Ultrasmall Nanoparticles for Multifunctional Deep‐Tissue Photothermal Therapy

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription properties of neodymium ions in NdVO4 and of the high neodymium content) as well as to their ultrasmall size that leads to large non-radiative decay rates. Results included in this work introduce to the scientific community ultrasmall NdVO4 stoichiometric nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…The photothermal effect was attributed to the strong absorption of Nd 3+ ions. Similar photothermal effects were also found in other Nd 3+ doped/based nanoparticles …”
Section: Applicationssupporting
confidence: 83%
“…The photothermal effect was attributed to the strong absorption of Nd 3+ ions. Similar photothermal effects were also found in other Nd 3+ doped/based nanoparticles …”
Section: Applicationssupporting
confidence: 83%
“…Notably, metallic NPs can transport a therapeutic dose of heat under low exposures of extracorporeally applied light in the near‐infrared (NIR) spectrum. This may be applicable to photothermal therapy‐based cancer treatment . Therefore, a question arises: can a similar mechanism increase the photothermal heating efficiency of PCMs?…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, B. del Rosal et al have demonstrated the promising potentiality of ultrasmall stoichiometric (100% mol. Nd) NdVO 4 (2.4 nm) NPs for highly efficient deep-tissue photothermal therapy [80]. This potentiality can be explained taking into account the large absorption cross section at 808 nm in NdVO 4 , the high Nd content and the ultrasmall size that leads to large non-radiative rates by exploiting the energy migration to surface killer mechanism described in Fig.…”
Section: Nd 3þ As Heating Ionmentioning
confidence: 99%